Combined use of nonculture-based lab techniques in the diagnosis and management of critically ill patients with invasive fungal infections. Issue 11 (November 2012) - Pemán, Javier; Zaragoza, Rafael
Invasive fungal infections are associated with high morbidity and mortality in critically ill patients due, in part, to diagnostic difficulties in the early stages. Nonculture-based techniques such as (1, 3)-β-d -glucan, galactomannan, mannan and antimannan antibodies, Candida albicans germ tube-specific antibodies or fungal DNA are required for earlier diagnosis, prognostic information and monitoring outcome. A decision-tree algorithm based on the combination of nonculture-based techniques is suggested to optimize the diagnosis and evolution of critically ill patients at risk of invasive mycoses. The use of (1, 3)-β-d -glucan and blood cultures twice a week is proposed; if positive, treatment initiation is recommended alongside the performance of the nonculture-based microbiological tool depending on suspected mycoses and the availability of techniques.